Women prefer proactive support from providers for treatment of heavy menstrual bleeding: A qualitative study in adult women with moderate or severe Von Willebrand disease. Issue 6 (10th July 2018) - Eising, H. P.; Sanders, Y. V.; de Meris, J.; Leebeek, F. W. G.; Meijer, K.
Abstract : Objective: To explore key factors for successful support in women with moderate or severe Von Willebrand disease (VWD) who are faced with heavy menstrual bleeding (HMB) and surgery. Design: A qualitative study design with focus‐group interviews and thematic analysis of the discussions. Settings and population: Eleven VWD women aged 41‐68 years (median age 58 years) who had had a hysterectomy or bipolar radiofrequency ablation (BRA) because of HMB participated in this study. Three of the 11 participants had VWD diagnosed before surgery. Two focus groups were conducted in the summer of 2012. Patients were identified through participation in a nationwide study on Von Willebrand disease in the Netherlands (WiN study). Inclusion criteria were at least 18 years of age, fluent in Dutch, diagnosed with VWD (based on Von Willebrand factor (VWF) antigen and/or activity levels < 30 IU/dL) and previous surgical therapy for HMB. Findings: The following key factors were identified during focus‐group interviews: receiving information, proactive support from providers and considering bleeding disorders as a cause of HMB. Other topics were as follows: experiences with VWD and/or surgery, how relieved patients were when menses stopped, patients hoped that in future, providers would work better together so that women receive the best care. Conclusions: In this focus‐group study among women with VWD who underwent surgery because of HMB, support by professionals could be improved by considering a bleeding disorder in women with HMB, providing information about different types of surgery and shared decision‐making regarding type of interventions.